2022
DOI: 10.1093/emph/eoac017
|View full text |Cite
|
Sign up to set email alerts
|

Squatting, pelvic morphology and a reconsideration of childbirth difficulties

Abstract: Childbirth is commonly viewed as difficult in human females, encompassed by the “Obstetrical Dilemma” (OD) described by early palaeoanthropologists as an evolved trade-off between a narrow pelvis necessitated by bipedalism and a large-brained fetal head. The OD has been challenged on several grounds. We add to these challenges by suggesting humans likely squatted regularly during routine tasks prior to the advent of farming societies and use of seats. We suggest that habitual squatting, together with taller st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 97 publications
0
5
0
Order By: Relevance
“…Moreover, greater pelvic breadth in females has been shown to yield additional speed flexibility and greater stride length, partly compensating for elevated locomotor costs owing to lower hip mechanical advantage (Gruss et al, 2017; Rak, 1991; Wall‐Scheffler, 2022; Wall‐Scheffler & Myers, 2017; Whitcome et al, 2017). These results led several authors to reject the hypothesis that efficient bipedal locomotion has restricted the evolution of a more spacious birth canal (e.g., Dunsworth, 2016, 2018; Warrener et al, 2015, Warrener, 2018; Gorman et al, 2022). Some authors questioned (Nowell & Kurki, 2020; Warrener et al, 2015) or even rejected (e.g., Dunsworth, 2018, 2021; Gorman et al, 2022) the entire notion of an evolutionary tradeoff subsumed under the classic obstetrical dilemma hypothesis.…”
Section: There Is Strong Empirical Evidence Of Functional Tradeoffs A...mentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, greater pelvic breadth in females has been shown to yield additional speed flexibility and greater stride length, partly compensating for elevated locomotor costs owing to lower hip mechanical advantage (Gruss et al, 2017; Rak, 1991; Wall‐Scheffler, 2022; Wall‐Scheffler & Myers, 2017; Whitcome et al, 2017). These results led several authors to reject the hypothesis that efficient bipedal locomotion has restricted the evolution of a more spacious birth canal (e.g., Dunsworth, 2016, 2018; Warrener et al, 2015, Warrener, 2018; Gorman et al, 2022). Some authors questioned (Nowell & Kurki, 2020; Warrener et al, 2015) or even rejected (e.g., Dunsworth, 2018, 2021; Gorman et al, 2022) the entire notion of an evolutionary tradeoff subsumed under the classic obstetrical dilemma hypothesis.…”
Section: There Is Strong Empirical Evidence Of Functional Tradeoffs A...mentioning
confidence: 99%
“…These results led several authors to reject the hypothesis that efficient bipedal locomotion has restricted the evolution of a more spacious birth canal (e.g., Dunsworth, 2016, 2018; Warrener et al, 2015, Warrener, 2018; Gorman et al, 2022). Some authors questioned (Nowell & Kurki, 2020; Warrener et al, 2015) or even rejected (e.g., Dunsworth, 2018, 2021; Gorman et al, 2022) the entire notion of an evolutionary tradeoff subsumed under the classic obstetrical dilemma hypothesis.…”
Section: There Is Strong Empirical Evidence Of Functional Tradeoffs A...mentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that the SI joint has a physiological movement from 2 mm to 4 mm [ 32 34 ]. The fully threaded screws in group FT could have provided an overly rigid structure impeding the physiological movement of the SI joint.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have found there is an association between the two ( 7 , 18 ), while others have not ( 1922 ). Another point of debate revolves around whether differential birth canal proportions are associated with obstruction during delivery ( 714 , 17 , 2326 ). Recently, there has been growing appreciation for the concept of a multifactorial pelvis, which proposes that the role of pelvic width reduction is not just to enable bipedal locomotion, but also to reduce the risk of pelvic floor disorders.…”
Section: Introductionmentioning
confidence: 99%